[Petroscam ; Smokey Mountain - Lazaro, Cheche (The Probe Team : [episode no. 104], 1990)
A look at Joker Arroyo accusing Sec. Concepcion of DOTC of pressuring government banks to give " behest" loans. Also how the singing group was formed by Ryan Cayabyab and became a hit because their songs are of serials social issues. Includes also interviews with Geneva Cruz, James Coronel, Jeffrey and Tony.